CITRA ISTRI DALAM NOVEL INDONESIA DAN MALAYSIA: STUDI PADA ENTROK KARYA OKKY MADASARI DAN ANUGERAH BUAT SYAMSIAH KARYA ROHANI DIN - Pradika Ayu Lestari; Anas Ahmadi; Resdianto Permata Raharjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study uses a qualitative approach to describe the image of the wife in two novels: "Entrok" by Okky Madasari (Indonesia) and "Anugrah Buat Syamsiah" by Rohani Din (Malaysia). Data were collected through interviews, document analysis, and behavioral observation, with a focus on expressions and dialogues that reflect the wife's struggles in family decision-making. This study examines the cultural background and feminist issues based on Gayatri Spivak's subaltern feminist theory. The methodology consists of three steps: a literature review to understand the context of feminism and women's roles, systematic note-taking to organize the data, and grouping the content into relevant themes. Analytical techniques include reading quotations, grouping the data, and linking the analysis to subaltern feminist theory. The results show that both novels depict the complexity of the wife's role in a patriarchal society, as well as the challenges faced in striving for freedom and autonomy. Thus, this study contributes to a deeper understanding of the representation of women in literature and the relevance of feminist theory in the Indonesian and Malaysian contexts.